Circulating nerve growth factor receptor positive cells are associated with severity and prognosis of pulmonary arterial hypertension - Chiaki Goten; Soichiro Usui; Shin-ichiro Takashima; Oto Inoue; Hirofumi Okada; Masaya Shimojima; Kenji Sakata; Masaaki Kawashiri; Shuichi Kaneko; Masayuki Takamura (Pulmonary Circulation, 2021)
Pulmonary arterial hypertension (PAH) remains a disease with a poor prognosis, so early detection and treatment are very important. Sensitive and non-invasive markers for PAH are urgently required. This study was performed to identify sensitive markers of the clinical severity and prognosis of PAH. Patients diagnosed with PAH (n = 30) and control participants (n = 15) were enrolled in this observational study. Major EPC and MSC markers (including CD34, CD133, VEGFR2, CD90, PDGFRα, and NGFR) in peripheral blood mononuclear cells (PBMNCs) were assessed by flow cytometry. Associations of these markers with hemodynamic parameters (e.g. mean pulmonary arterial pressure, pulmonary vascular resistance, and cardiac index) were assessed. Patients with PAH were followed up for 12 months to assess the incidence of major adverse events, defined as death or lung transplantation. Levels of circulating EPC and MSC markers in PBMNCs were higher in patients with PAH than in control participants. Among the studied markers, nerve growth factor receptor (NGFR) was significantly positively correlated with hemodynamic parameters. During the 12-month follow-up period, major-event-free survival was significantly higher in patients with PAH who had relatively low frequencies of NGFR positive cells than patients who had higher frequencies. These results suggested that the presence of circulating NGFR positive cells among PBMNCs may be a novel biomarker for the severity and prognosis of PAH.